Analysis of Three Dimensional Thermal and Flow Fields for the Brushless Exciter with Full Axial Ventilation under Multi-scheme - HAN Jia-de; ZHANG Yu-nan; LIU Yan-hao; LI Hui-lan; LU Yi-ping; FU Xiu-lan (Journal of Harbin University of Science and Technology)
According to the existing scheme of 7.8MW brushless exciter , the ventilation and cooling system is optimized and a variety of schemes are proposed to change the ventilation structure, rotation direction and inlet position of the present scheme in this paper.The fluid-solid coupling model of the whole machine is established. ?Numerical calculation of heat flow field of exciter under multi-scheme is made and compared by adopting the finite volume method and giving boundary conditions based on the principle of computational fluid dynamics. ?Changing the ventilation structure of the present scheme, the results show that the distribution law of air pressure, the velocity and temperature in exciter are basically the same as that of current operation, the average temperature of stator and rotor parts is different, and the maximum temperature remains at the end of the rotor bar far from the rectifier panel and is lower than the maximum temperature of the original scheme. Exchanging inlet and outlet position under present scheme, it has a great influence on the heat flux field of the exciter, and the maximum temperature is at the end of the stator bar near the rectifier plate.The research results provide theoretical guidance for the optimal design of the exciter with similar structure.